Examining the Relationship between Community Participation and Program Outcomes in a Metaevaluation - Nkwake, Apollo M; Trandafili, Holta; Hughey, Joel (Journal of MultiDisciplinary Evaluation, 2013)
Background: The salience of stakeholder participation in community development is not disputed. However, there is a paucity of evidence that clearly links participation with program outcomes. Purpose: We examined the link between participation and program outcomes. Setting: The article discusses data collated from World Vision (WV) program evaluations. WV is a faith based, grass-root community engaging, child focused relief and development organization that works in close to 100 countries to improve and sustain child well-being. Community participation is very central to WV’s program. Intervention: 92 community development programs evaluated between 2005 and 2010. Research Design: We used a metaevaluation design (Meta-analysis Summaries [DeCoster, 2004]), which involves identifying the prevalence of certain effects (such as child well-being outcomes) and the strengths of relationships among those effects and certain explanatory variables (such as community participation). Data Collection and Analysis: A document review tool comprising 327 variables was used to review program design documents and evaluation reports. Each review item generated a score whenever a positive response was checked. The maximum possible score for a program was 200. These scores were used to measure correlations among major variables of participation and program outcomes. After the program documents were reviewed, the data was then manually entered into PASW statistics for analysis. Findings: Programs that mostly used empowering approaches engaging a higher level of stakeholder participation were more than fifteen times more likely to exhibit improvements in child health, community health, education, and protection outcomes than those that which used direct service delivery (give a fish) approaches engaging less stakeholder participation. Also, participation of vulnerable groups like children and women had a stronger relationship with program outcomes than other forms of participation that did not involve vulnerable groups.